1999
DOI: 10.1124/mol.55.6.993
|View full text |Cite
|
Sign up to set email alerts
|

Residues in Transmembrane Domains I and II Determine γ-Aminobutyric Acid Type AAReceptor Subtype-Selective Antagonism by Furosemide

Abstract: GABAA receptors in cerebellar granule cells are unique in expressing a subtype containing the alpha6 subunit. This receptor subtype has high affinity for GABA and produces a degree of tonic inhibition on cerebellar granule cells, modulating the firing of these cells via spillover of GABA from GABAergic synapses. This receptor subtype also has selective affinity for the diuretic furosemide over receptors containing other alpha-subunits. Furosemide exhibits approximately 100-fold selectivity for alpha6-containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 13 publications
2
51
0
Order By: Relevance
“…In fact, the use of Xenopus oocytes to characterize recombinant mammalian GABA A Rs dates back to the 1980s (55,56). Since then, numerous studies have used this expression system to characterize particular GABA A R subunit compositions in functional and pharmacological terms (57)(58)(59)(60). Moreover, biochemical regulation of recombinant GABA A R expression has often been studied in oocytes (61,62), and it has been demonstrated that these receptors, either expressed in human embryonic kidney cells or in Xenopus oocytes, are similarly modulated by PKC (63).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the use of Xenopus oocytes to characterize recombinant mammalian GABA A Rs dates back to the 1980s (55,56). Since then, numerous studies have used this expression system to characterize particular GABA A R subunit compositions in functional and pharmacological terms (57)(58)(59)(60). Moreover, biochemical regulation of recombinant GABA A R expression has often been studied in oocytes (61,62), and it has been demonstrated that these receptors, either expressed in human embryonic kidney cells or in Xenopus oocytes, are similarly modulated by PKC (63).…”
Section: Discussionmentioning
confidence: 99%
“…A number of allosteric modulators demonstrate b-subunit selectivity, for example, loreclezole, etomidate, furosemide Hill-Venning et al, 1997;Thompson et al, 1999). Regardless of whether the compound inhibits (e.g.…”
Section: Interaction With Other Gaba a Receptor Ligandsmentioning
confidence: 99%
“…In recent years, a number of modulators of the GABA A receptor have been reported that demonstrate b2/3 selectivity over b1, for example, loreclezole, etomidate, tracazolate, mefenamic acid, furosemide Hill-Venning et al, 1997;Halliwell et al, 1999;Thompson et al, 1999;. In all cases, the potency of the modulator was reduced or abolished when serine was introduced into b2 or b3 (position 289 in human b2 and 290 in human b3) and increased or conferred when asparagine was introduced into b1 (position 290).…”
Section: Comparison With Other B-selective Compoundsmentioning
confidence: 99%
“…It has previously been suggested that these processes are coupled together functionally and structurally (Boileau and Czajkowski, 1999;Thompson et al, 1999;Carlson et al, 2000;Kash et al, 2003;Miyazawa et al, 2003). In the nicotinic AChR (nAChR), as in all other members of the cys-loop superfamily of LGICs, the ligand-binding domain is located between two subunit interfaces (␣/␥ and ␣/␦ for nAChRs) in the extracellular N termini, and gating occurs in the pore-lining M2 segment.…”
Section: Discussionmentioning
confidence: 99%